Local Wisdom Values of Arakan Sahur, Takbiran, and Hadrah Tradition in Kuala Tungkal, Tanjung Jabung Barat (An Ethnolinguistics Study) - Afria, Rengki; Chotimah, Khusnul; Izar, Julisah; Fatrizal, Fatrizal; Fardinal, Fardinal; Maharja, Syafria (Titian: Jurnal Ilmu Humaniora, 2025)
ndonesia has a variety of cultures and local wisdom. One of the local wisdoms is the tradition carried out by an ethnic group. As a country that has a cultural diversity, there are many traditions carried out by local communities in Indonesia. for example, in Kuala Tungkal, Tanjung Jabung Barat, Jambi Province. Kuala Tungkal is an area that is still in attached to its traditions. This research aims to describe local wisdom in the traditions in Kuala Tungkal, namely arakan sahur, takbiran, and hadrah tradition. This research is included in the type of qualitative descriptive research. The data in this research are in the form of the arakan sahur, takbiran, and hadrah tradition. Based on the result of disscussuon, the Kuala Tungkal Muslim community rejoices in welcoming Islamic holidays and without any doubt shows the public to uphold their Malayness. Abstrak Indonesia memiliki beragam budaya (culture) dan kearifan lokal (local wisdom). Salah satu kearifan lokal adalah tradisi-tradisi yang dilakukan oleh sekelompok etnis. Sebagai negara yang memiliki keragaman budaya, terdapat banyak sekali tradisi-tradisi yang dilakukan oleh masyarakat-masyarakat di daerah di Indonseia. Misalnya di daerah Kuala Tungkal, Kabupaten Tanjung Tajung Barat, provinsi Jambi. Kuala Tungkal merupakan daerah yang masih lekat dengan tradisinya. Penelitian ini bertujuan mendeskripsikan kearifan lokal pada tradisi-tradisi yang ada di Kuala Tungkal yaitu Arakan Sahur, Takbiran, dan Hadrah Tradisi. Penelitian ini termasuk dalam jenis penelitian deskriptif kualitatif. Data pada penelitian ini berupa tradisi arakan sahur, takbiran dan hadrah tradisi. Berdasarkan hasil pembahasan masyarakat muslim Kuala Tungkal yang bersuka ria menyambut hari-hari besar Islam dan tanpa ada keraguan menunjukkan kepada khalayak untuk menjunjung tinggi kemelayuannya.